We are not alternative facts: feeling, existing, and resisting in the era of Trump. Issue 10 (26th November 2017) - E. Castrellón, Liliana; Reyna Rivarola, Alonso R.; López, Gerardo R.
Abstract: In this article the authors argue that Donald Trump is not simply a presidential figure, but the embodiment of white supremacy, capitalism, racism, neoliberalism, patriarchy, xenophobia, Islamaphobia, homophobia, and more. It is our belief that historically marginalized communities are in a state of constant terror as we try to make sense of how to navigate, live, and merely exist in a world where our livelihood is constantly under threat. In this article, we aim to showcase some of the ways in which people in our communities are coping and making sense of Trump's presidency and his spiteful rhetoric. The authors include personal reflections, and weave in art, poems, and Facebook statuses of Students of Color who are also responding to the current administration. By meshing many perspectives, we seek to understand glimpses of the totality and impact of this president in our daily lives.